Analysis of the Adoption Rate of BATAN Mutant Rice Varieties in the Musi Rawas Area - Zaini Amin; andry andry; Edy Humaidi (Jurnal Penelitian Pertanian Terapan, 2022)
The adoption of innovations of superior mutant rice varieties expected to help communities overcome hunger and food insecurity by providing easier access to food for poor people in rural areas. The purpose of this study is to determine the level of adoption of farmers for irradiated rice and analyze the factors that influence farmers in adopting irradiated rice. This research was conducted from October to November 2018 in Musi Rawas Regency using a survey method. Data obtained from interviews with 75 farmers who have applied the mutant variety. Survey data obtained were analyzed using SEM. The results showed that the technology adoption rate of mutant rice varieties reached the experimental stage; and There are three latent constructs that are significantly (ρ <0.01) positively correlated, namely: farmer preference (X2) to adoption rate (Y1), support of extension agent (X5) to farmer characteristics (X1) and farmer preference (X2).